2018
DOI: 10.2196/jmir.9222
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cases of Noncompliance to Drug Treatment in Patient Forum Posts: Topic Model Approach

Abstract: BackgroundMedication nonadherence is a major impediment to the management of many health conditions. A better understanding of the factors underlying noncompliance to treatment may help health professionals to address it. Patients use peer-to-peer virtual communities and social media to share their experiences regarding their treatments and diseases. Using topic models makes it possible to model themes present in a collection of posts, thus to identify cases of noncompliance.ObjectiveThe aim of this study was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Automatic and manual extraction methods were utilized, depending on the source of the posts. For generic French medical web forums, posts were automatically extracted using the Detec’t WebCrawler [ 22 ]. Collection of the posts was performed according to the HTML structure of each forum.…”
Section: Methodsmentioning
confidence: 99%
“…Automatic and manual extraction methods were utilized, depending on the source of the posts. For generic French medical web forums, posts were automatically extracted using the Detec’t WebCrawler [ 22 ]. Collection of the posts was performed according to the HTML structure of each forum.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Abdellaoui et al , 9 outlined a methodology to detect medication non-compliance behaviours amongst people on antidepressant and antipsychotic medications by modelling the way dosage variation and treatment interruption behaviours were discussed online. Jones et al , 10 demonstrated it was possible to uncover the hidden, less obvious aspects of breast cancer management and recovery in online discussion forums, including aspects that are not easily ascertainable in patient clinics (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The hybrid approach is a combination of the two methods. 19 The topic modelling approach has been previously adopted by medical researchers to identify patterns of comorbid medical conditions, 20 detect medication noncompliance using posts in patient forums, 21 describe public health information from the social media, 22 cluster analysis of large biomedical datasets 23 and predict inpatient clinical order patterns. 24 The method used in this study assigns words to topics (themes) based on the probability of membership of the topic but the clinical interpretation of the topic is still needed.…”
Section: Discussionmentioning
confidence: 99%